2015
DOI: 10.4049/jimmunol.1500485
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Inflammatory Cytokines Induce Selectin Ligand Expression on Murine CD4 T Cells via p38α MAPK

Abstract: Selectins are glycan-binding adhesion molecules which mediate the initial steps of leukocyte recognition of endothelium. Cytokines control numerous aspects of CD4 T helper differentiation, but how cytokines control induction of ligands for E- and P-selectin on T helper subsets remains poorly understood. Among 20 cytokines that affect T helper cell differentiation, we identified six, IL-12, IL-18, IL-27, IL-9, IL-25 and TGFβ1, that induce expression of selectin ligands on murine CD4 T cells above the low levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…1I) (20), and this is also observed with other cytokines (20). The basis for this pattern of expression has never been determined, but could potentially be explained by a threshold of TGF-b1 signal strength required for induction of selectin ligands.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…1I) (20), and this is also observed with other cytokines (20). The basis for this pattern of expression has never been determined, but could potentially be explained by a threshold of TGF-b1 signal strength required for induction of selectin ligands.…”
Section: Resultsmentioning
confidence: 83%
“…Loss of both Smad2 and Smad3 in conventional T cells leads them to be refractory to TGF-b1-mediated inhibition, leading to similar pathology (10,21). In addition to a role in Th cell differentiation, TGF-b1 is a potent inducer of E-and P-selectin ligands in CD4 T cells, both in humans and mice (19,20). We have recently shown that this induction of selectin ligands requires p38a MAPK (20), one of several non-Smad pathways activated by TGFb1 (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations